2018
DOI: 10.1590/rbz4720170114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sumac and turmeric as feed additives on performance, egg quality traits, and blood parameters of laying hens

Abstract: The objective of this study was to investigate the effects of sumac and turmeric on performance, egg quality traits, and blood parameters of laying hens. Forty Lohman Brown hens at 30 weeks of age were distributed into four groups, consisting of five replicates with two hens in each. The experiment lasted for 42 days. Laying hens were fed different basal diets in treatment groups and control groups. The groups consisted of hens fed a basal diet with 0.5% sumac, a basal diet with 0.5% turmeric, and a basal diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
5
20
3
5
Order By: Relevance
“…Previous studies have found reduced body weight at higher feeding rates than in this study [23]. Other studies with poultry have found reduced egg weight at relatively low levels [26], confirming reduced production in chickens. Thyme also reduced feed intake in our study, but only at 2%.…”
Section: Feed Intake and Growthsupporting
confidence: 77%
See 3 more Smart Citations
“…Previous studies have found reduced body weight at higher feeding rates than in this study [23]. Other studies with poultry have found reduced egg weight at relatively low levels [26], confirming reduced production in chickens. Thyme also reduced feed intake in our study, but only at 2%.…”
Section: Feed Intake and Growthsupporting
confidence: 77%
“…From these seven treatment groups, 1 bird/replicate was used for blood sampling, for immunity parameters a different bird was used from each replicate, and for carcass samples yet another bird was used from each replicate. The birds in the control group were given the basal diet, while those in treatment groups were given supplements as detailed below: Treatment 1: Basal diet (control); T1: Basal diet + thyme powder at 1% from days 29-42 T2: Basal diet + thyme powder at 2% from days 29-42 T3: Basal diet + thyme powder at 3% from days 29-42 S1: Basal diet + sumac powder at 1% from days 29-42 S2: Basal diet + sumac powder at 2% from days 29-42 S3: Basal diet + sumac powder at 3% from days [29][30][31][32][33][34][35][36][37][38][39][40][41][42] The basal diet consisted of a three-phase feeding program: starter feed from d 1-7, grower feed from d 8-24, and finisher feed from d [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The ingredients and nutrient composition of the diets are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…O extrato de flor de marigold (Tagetes erecta) contém 12 g/kg de xantofilas, sendo 80 a 90% de luteína, um carotenoide amarelo. A páprica (Capsicum annuum) tem de 4 a 8 g/ kg de xantofilas, sendo 50 a 70% capsantina, um pigmento vermelho-alaranjado (GUMUS et al, 2018). Estes carotenoides advindos da alimentação são depositados fisiologicamente na gema do ovo.…”
Section: Introductionunclassified